The injury incidence and treatment experience among elite and beginner Thailand bodybuilders - Nur Ikhwan Mohamad (Tanjung Malim, 2023)
The injury incidence and treatment experience among elite and beginner Thailand bodybuilders by Nur Ikhwan Mohamad